Analysis of Enterprise Management Software Development and Project Management Based on DevOps - Zhang, Qinhong; Zhang, Chundong (International Journal of Mechanical and Electrical Engineering, 2025)
In the process of enterprise software development, traditional development and operations models face challenges such as low release efficiency and poor stability. This research explores the application of DevOps theory in enterprise management software development and project management. Through literature review and case analysis, the core principles and practices of DevOps are systematically explained, with a focus on the implementation strategies of key components such as continuous integration, automated testing, and monitoring feedback. The study finds that DevOps can effectively improve software delivery efficiency and enhance system stability. Using an e-commerce platform as a case study, the implementation of DevOps significantly improved release efficiency and system availability. The results provide a theoretical basis and practical reference for enterprises to implement DevOps transformation.